Legal Learning Strategies for Early Childhood: A Conceptual Approach to Instilling Legal Values and Awareness from an Early Age - Fitri, Fitri; Afriadi, Bambang; Humulhaer, Siti (IJBLE Scientific Publications Community Inc., 2024)
Legal education for early childhood plays an important role in shaping legal awareness from an early age, which contributes to compliance with social rules in the future. This study uses a normative research method with a Systematic Literature Review (SLR) approach to identify and synthesise effective methods for teaching legal concepts in early childhood. This study analyses various previous studies that highlight Piaget's theory of cognitive development, Vygotsky's theory of social learning, and Gardner's concept of multiple intelligence in the context of legal learning. Several studies show that experiential learning-based approaches, gamification, mini-court simulations, and legal narratives are able to increase children's understanding of legal and social norms. A character-based approach and moral values, as affirmed by Lickona, have been proven to shape children's legal awareness more deeply. By compiling a conceptual synthesis of various pedagogical approaches, this study provides practical recommendations for educators and policymakers in designing more effective legal learning strategies for early childhood.